Provisions for the Seismic Risk Evaluation of Existing Reinforced Concrete Buildings in Turkey under the Urban Renewal Law. Issue 3 (August 2015) - Binici, Baris; Yakut, Ahmet; Ozcebe, Guney; Erenler, Atila
A law known as the "Urban Renewal Law" for risk mitigation was passed in Turkey in May 2012. The major focus of the law is to reduce the expected seismic risk due to the vulnerability of existing buildings. For this purpose, new provisions are set forth to investigate and to classify seismically vulnerable residential buildings as quickly as possible. Afterward, such deficient buildings are demolished, and new buildings are constructed through the financing options provided by the government. Although the strengthening of deficient buildings still remains an option, it is not encouraged, especially for older structures with critical deficiencies. In this article, the technical provisions for seismic risk assessment are presented. Special emphases are given to member ductility and deformation limits to be used in linear elastic assessment procedures. A simple procedure, given as an option, to consider the beneficial presence of infill walls at low deformations is presented. Finally, results are given for case study buildings.